Analisis Analisis Faktor yang Memengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor dalam Membayar Pajak - Darmayanti, Ni Putu Dita; Lely Aryani Merkusiwati, Ni Ketut (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p19, 2024)
Tax is a source of state revenue and is a potential sector related to the success of national development. The aim of the research is to empirically prove the influence of tax knowledge, moral obligations and tax socialization on taxpayer compliance. The research was conducted at the SAMSAT Bangli Office. The sampling method used non-probability sampling, namely incidental sampling, data was collected using a survey method with questionnaire techniques and analyzed using multiple linear regression analysis techniques. The research results show that tax knowledge, moral obligations and tax socialization have a positive and significant effect on taxpayer compliance. Keywords: Tax Knowledge; Moral Obligation; Tax Dissemination; Taxpayer Compliance